(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Analyzing the factors affecting the health insurance reimbursement results of Sai Gon General Hospital in the period 2018-2020. Method: Employing qualitative design. In-depth interviews were conducted with 12 key informants, including one member from the Board of Directors, 04 heads of the functional department, 05 heads of the clinical department, doctors and nurses, 02 provincial social security agency staff. Results: The study confirms that some factors affecting the health insurance reimbursement results to the hospital have been indicated in the national literature. The driven factors could be categorized into four main groups: factors related to state management agencies, factors related to social health insurance agencies, factors related to hospitals, and factors belonging to insured patients. Conclusions: The results on the hospital-related factors are beneficial to help improve the reimbursement results of the hospital in the upcoming period.